Corporate Social Responsibility for the Social Welfare of the Target Group - Oktaviana, Nia Shinta; Agustina, Isna Fitria (Universitas Muhammadiyah Sidoarjo, 2020)
The results of the study indicate that the implementation of the CSR Program for Community Social Welfare can be said to be in accordance with the conditions in the field. The target group is one of the foundations caring for children with special needs and the foundation for fostering disabled children in Surabaya. And the supporting factors of this application are the community and the agency, while the inhibiting factor of this application is the frequent shortage of crew when implementing CSR programs. company power. The purpose of this study is to find out more about the implementation of CSR programs for the welfare of the target group. This research method uses descriptive qualitative, data collection is done by observation, interviews, documentation and literature review. The technique of determining the informants used purposive sampling. The informants in this research are Tax & CSR Division, Assistant Manager of Public Relations, Peduli Kasih Foundation for Children with Special Needs, YPAC. The analysis technique of this research is qualitative. The results of the study indicate that the implementation of the CSR Program for Community Social Welfare can be said to be in accordance with the conditions in the field. The target group is one of the foundations caring for children with special needs and the foundation for fostering disabled children in Surabaya. And the supporting factors of this application are the community and the agency, while the inhibiting factor of this application is the frequent shortage of crew when implementing CSR programs.